Business Information Systems 15th International Conference, BIS 2012, Vilnius, Lithuania, May 21-23, 2012. Proceedings - Abramowicz, Witold; Kriksciuniene, Dalia; Sakalauskas, Virgilijus; SpringerLink (Online service) (Berlin, Heidelberg : Springer Berlin Heidelberg, 2012)
This book contains the refereed proceedings of the 15th International Conference on Business Information Systems, BIS 2012, held in Vilnius, Lithuania, in May 2012.The 26 revised full papers were carefully reviewed and selected from 70 submissions. They are grouped into nine sessions on business process discovery, business process verification, service architectures, collaborative BIS, data management, Web search applications, BIS in finance, decision support, and specific BIS issues. The volume is completed by an invited paper on "Information Systems and Business and Information Systems Engineering."
Keywords: Economics; Information storage and retrieval systems; Management information systems; Economics/Management Science; Business Information Systems; Information Systems Applications (incl. Internet).; Information Storage and Retrieval